FAKTOR-FAKTOR YANG MEMENGARUHI KUALITAS PEMERIKSAAN (Studi Pada Auditor BPK Perwakilan Jawa Timur) - - Faizah; Rahmat Zuhdi (JAFFA, 2013)
The purpose of this research is to analyze of the audit quality factors. The units analysis of this research are auditors in Indonesian Audit Board (BPK) representative at East Java. The data of this research were collected by using questionnaires to the auditors BPK representative at East Java. The sampling method used simple random sampling. The data had been analyzed to test the hypothesis using the Multiple Regression Analysis.The results of this results showed that: 1) partially, independence and integrity of a significant effect on audit quality; 2) simultaneously, objectivity, experience, knowledge, accountability, and professional skepticism not influence on the audit quality.